2020
DOI: 10.1002/jgh3.12303
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in patients with acute upper gastrointestinal bleeding following changes to management protocols at an Australian hospital

Abstract: Background and Aim Upper gastrointestinal bleeding (UGIB) has a high mortality rate and requires efficient and directed acute management. This project aimed to assess patient outcomes following changes to UGIB management protocols at Northern Hospital, Victoria, Australia. Changes involved streamlining management under a single inpatient unit, earlier endoscopy, blood transfusion thresholds, and risk stratification. Methods This was a cohort study of 400 patients aged ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Functional gastrointestinal disorders (FGIDs) are common unexplained gastrointestinal symptoms that are thought to arise from different locations of the digestive tract. Two of the recognized diseases are functional dyspepsia and irritable bowel syndrome (IBS) [1]. Functional dyspepsia is a complex collection of symptoms from the gastroduodenal part of the digestive tract and includes pain or burning sensation in the epigastrium, a feeling of fullness after eating, or an early feeling of fullness [2].…”
Section: Introductionmentioning
confidence: 99%
“…Functional gastrointestinal disorders (FGIDs) are common unexplained gastrointestinal symptoms that are thought to arise from different locations of the digestive tract. Two of the recognized diseases are functional dyspepsia and irritable bowel syndrome (IBS) [1]. Functional dyspepsia is a complex collection of symptoms from the gastroduodenal part of the digestive tract and includes pain or burning sensation in the epigastrium, a feeling of fullness after eating, or an early feeling of fullness [2].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, if the patient is receiving antiplatelet agents or has coagulopathy, endoclips are safer than thermal coagulation because they cause less tissue damage. [5] Several recent studies have demonstrated that large amounts of epinephrine injections are superior to small amounts of injections in recurrent bleeding in peptic ulcers. These studies suggest that local tamponade has the greatest effect on continuous hemostasis, and that larger volumes of epinephrine injection may prevent re-bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical compression of the hemorrhaging vessel in peptic ulcer is the key factor for achieving initial hemostasis. In addition, if the patient is receiving antiplatelet agents or has coagulopathy, endoclips are safer than thermal coagulation because they cause less tissue damage [5] . Several recent studies have demonstrated that large amounts of epinephrine injections are superior to small amounts of injections in recurrent bleeding in peptic ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…Adding further perspective to these observations, in this issue of JGH Open , Nagarethinam et al report a cross‐sectional survey assessing the prevalence and associations of FGIDs among HCPs from a tertiary Australian hospital setting 8 . Between January 2017 and June 2018, 274 HCPs were surveyed, and data were collected for demographics, medical role, work hours, sleep habits, stress levels (frequency and severity), and dietary factors.…”
mentioning
confidence: 99%
“…Adding further perspective to these observations, in this issue of JGH Open , Nagarethinam et al report a cross‐sectional survey assessing the prevalence and associations of FGIDs among HCPs from a tertiary Australian hospital setting. 8 Between January 2017 and June 2018, 274 HCPs were surveyed, and data were collected for demographics, medical role, work hours, sleep habits, stress levels (frequency and severity), and dietary factors. Risk factors for FGIDs and their symptoms based on the Rome III criteria were assessed using a self‐report questionnaire (FGID‐Q), and quality of life (QoL) was assessed for its impact on work, leisure, relationships, and social activities.…”
mentioning
confidence: 99%